Probing the hydrolytic reactivity of 2-difluoromethyl pyrroles. Issue 1 (14th November 2016) - Melanson, Jennifer A.; Figliola, Carlotta; Smithen, Deborah A.; Kajetanowicz, Aleksandra K.; Thompson, Alison
Abstract : α-Difluoromethyl pyrroles were found to be stable while N -protected with an electron-withdrawing group. Abstract : α-Difluoromethyl pyrroles were found to be stable while N -protected with an electron-withdrawing group. Due to the propensity of pyrroles to access azafulvenium-like intermediates, the C–F bonds of an α-difluoromethyl substituent are labile under hydrolytic conditions. The presence of certain electron-withdrawing substituents about the pyrrolic ring can accelerate this process, as determined through a kinetic comparison of the deprotection and subsequent hydrolysis reactions of N -protected β-aryl α-difluoromethyl pyrroles.